Value-added tax and its efficiency: EU-28 and Turkey - Sabina Hodzic; Hulya Celebi (UTMS Journal of Economics, 2017)
This paper analyses value-added tax (VAT), with special emphasis on efficiency in the EU-28 Member States and Turkey, over the period from 2009 to 2013. From the results of the analysis, we concluded that, the highest efficiency ratio (50.8) was recorded in Croatia in 2013. This indicates that Croatia's value-added tax revenues as percentage of gross domestic product in the state budget were very high (12.7) in comparison to Turkey's (9.0) in 2013. As such, VAT is one of the most important taxes in the EU-28 Member States and many countries worldwide, like Turkey. The current VAT system in EU-28 Member States and Turkey is quite complex for the growing number of businesses operating cross-border. To increase investment, competitiveness and growth, an action plan on VAT is proposed for the creation of a single VAT area. The VAT system needs to be more efficient and simpler for businesses to use.
Keywords: H20; H25; 330; Value-added tax (VAT); tax efficiency; fiscal policy; tax system